Analysis of Crack Coalescence in Concrete Using Neural Networks - Haeri, H.; Sarfarazi, V.; Zhu, Z. (Проблемы прочности, 2016)
Fractures in the forms of joints and microcracks are commonly found in concretes, and their failure mechanism strongly depends on the crack coalescence pattern between pre-existing flaws. The determination of the failure behavior of nonpersistent joints is an engineering problem that involves several parameters as mechanical properties of concrete, normal stress and the ratio of joint surface to total shear surface. The impact of these parameters on the crack coalescence is investigated through the use of computational tools called neural networks. A number of networks of threshold logic units were tested, with adjustable weights. The computational method for the training process was a back-propagation learning algorithm. In this paper, the input data for crack coalescence consists of values of geotechnical and geometrical parameters. As an output, the network estimates the crack type coalescence (i.e., mode I, mode II, or mode I-II) that can be used for stability analysis of concrete structures. The performance of the network is measured and the results are compared to those obtained by means of experimental method. В местах разрушения бетонных конструкций часто обнаруживают макро- и микротрещины, причем на механизм их разрушения существенно влияет характер слияния трещин, выросших из исходных дефектов. Оценка характера разрушения неустойчивых связей является одной из инженерных задач, которая учитывает ряд параметров, включая механические характеристики бетона, уровень нормальных напряжений и соотношение между площадями поверхности дефектов и общей поверхности сдвига. Влияние этих параметров на слияние трещин оценивается с помощью расчетной методики нейронных сетей. Выполнено тестирование нескольких сетей с пороговыми логическими элементами и варьируемыми весовыми коэффициентами. Использовался обучающий алгоритм обратного распространения. В качестве входных данных по слиянию трещин использовались геотехнические и геометрические параметры, а в качестве выходных данных нейронная сеть выполняла оценку типа механизма слияния трещин (отрыва, сдвига или смешанной моды), который следовало использовать при анализе стабильности бетонных конструкций. Выполнена верификация расчетных результатов с помощью имеющихся экспериментальных данных. У місцях руйнування бетонних конструкцій часто виявляють макро- і мікротріщини, при цьому на механізм їх руйнування суттєво впливає характер злиття тріщин, що виросли з початкових дефектів. Оцінка характера руйнування нестійких зв'язків є однією з інженерних задач, яка враховує ряд параметрів, включаючи механічні характеристики бетону, рівень нормальних напружень і співвідношення між площами поверхні дефектів і загальною поверхнею зсуву. Вплив цих параметрів на злиття тріщин визначається за допомогою розрахункової методики нейронних сіток. Виконано тестування декількох сіток із пороговими логічними елементами і варійованими ваговими коефіцієнтами. Використовувався навчальний алгоритм зворотного розповсюдження. Вхідними даними по злиттю тріщин слугували геотехнічні і геометричні параметри, а вихідними нейронна сітка, за допомогою якої оцінювався тип механізму злиття тріщин (відрив, зсув або змішана мода), який використовувався при аналізі стабільності бетонних конструкцій. Виконано верифікацію розрахункових результатів за допомогою відомих експериментальних даних.